SARS-CoV-2 anti-spike antibodies after a fourth dose of COVID-19 vaccine in adult solid-organ transplant recipients. Issue 44 (19th October 2022) - Perrier, Quentin; Lupo, Julien; Gerster, Théophile; Augier, Caroline; Falque, Loïc; Rostaing, Lionel; Pelletier, Laurent; Bedouch, Pierrick; Blanc, Myriam; Saint-Raymond, Christel; Boignard, Aude; Bonadona, Agnès; et al.
Abstract: Background: A fourth dose of SARS-CoV-2 vaccine is recommended in solid-organ transplant (SOT) recipients, but the immunogenicity is poorly known. Methods: We conducted a retrospective, observational, monocentric study between the 1st January 2021 and 31st March 2022 of the anti-Spike antibody titers after one to four doses of vaccine in SOT. Results: 825 SOT were included. Median age at first vaccine injection was 61.2 (IQR 50.9–69.3) years; 66.7 % were male; 63.4 % had received four vaccine doses. The proportion of participants with a strong humoral response (>260 BAU/mL) increased with the number of vaccine doses: 10.6 % after the 1st dose (D1), 35.1 % after the 2nd (D2), 48.5 % after the 3rd (D3), and 65.1 % after the 4th (D4) ( p  < 0.001). Among the tested patients, the proportion with a detectable humoral response was significantly higher after D4 than after D3 (47 % vs 22 %, p  = 0.01). Liver transplant recipients had more frequently a strong humoral response after D2, D3 and D4 (OR = 5.3, 3.7 and 6.6 respectively when compared with other organ transplant recipients, p  < 0.001). In kidney transplant recipients, belatacept-containing regimen was associated with a lower rate of detectable humoral (9 % vs 40 %, p  = 0.025) after D3, but there was no statistical difference after D4. Conclusion: A fourth dose should be proposed to SOT recipients who did not developed an immune response after 3 doses. Kidney transplant recipients receiving belatacept have a poorer, although frequently detectable response.